Concrete construction handbook - Dobrowolski, Joseph A (McGraw-Hill handbooks, 1998)
This edition brings together more information on aspects of concrete technology and construction. It covers: high strength concrete; new additives such as silca fume; technical advances and techniques available; and codes and standards updates, including the 1995 concrete building code.